PENGARUH CITRA MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KIJANG INNOVA NON DIESEL (Studi kasus pada PT. Nasmoco Majapahit Semarang) - Leonardus Ardian Nugroho; Nawazirul Lubis; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2014)
With the increase of the upper middle class community in Indonesia, then the ability of purchasing power is also higher. It makes the car companies active in presenting new brands for the wishes of consumers fullfiled. Companies like Toyota sure that the brand is their identity of their products to different from competitors. To make the Toyota brand become a favourite consumer, the company is certainly doing promotional activities. From the sales result PT. Nasmoco Majapahit Semarang during the last 5 years, one of the product like a Kijang Innova Gasoline has a drop sales. Many factor cause a drop sales Kijang Innova Gasoline include brand image and promotion. This type of research used is explanatory research. The number of samples in this study was 90 respondents drawn by purposive sampling. Multiple regression analysis is Y = 3.804 + 0.192 X1 + 0.434 X2 so it can be seen that the variable brand image and promotion is jointly positive effect on variable purchase decisions, and which has the greatest influence is promotion variable. Hypothesis test shows that the brand image variable and promotion variable is effect on purchase decisions variable. This is demonstrated by the achievement of all the variable t is greater than t table is 1,9873. Brand image variables have t 9,022, and promotion variable have t 10,086. As for the F test obtained F count of 61,793. And all of these variables were tested at a significance level of 5 %. The advice for PT. Toyota Astra Motor is add GPS monitor in Kijang Innova Interior. With the equipment, consumer can easy to  get map while driving. From the promotion side, needs a creative promotion, that introduce brand with miniseries advertise. With miniseries advertise, brand of Toyota have a different from competitors.